Pengembangan Alper Silabu pada Materi Bilangan Bulat Kelas IV - Laurentius Pradipta Yudhautama; Novisita Ratu (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2019)
This study imns to teach the concept of integer addition and subtract operations in elementary schools by using ALPER SILABU. Using the ADDIE model consists of five phase (Analysis, Design, Development, Implementation, and Evaluation) to develop ALPER SILABU. ALPER SILABU has gone through tests of validity, practicality, and effectiveness. The results of ALPER SILABU validity obtained 97.6%, which means the media is valid. In practicality, the results of the study obtained 93.3% toal score which means the media is practical. The results of the field trials obtained an N-Gain score of 0.81 which is in the high category. The N-Gain results show that effective ALPER SILABU increases the understanding of students' concepts of integer addition and subtraction operations. Thus, the results of ALPER SILABU for teaching the concepts of addition operations and reduction in mathematical integers are valid, practical, and effective.